Mechanical properties of bamboo fibre biocomposite: a review / Anith Athierah Aziz, Sallehan Ismail and Siti Akhtar Mahayuddin - Aziz, Anith Athierah; Ismail, Sallehan; Mahayuddin, Siti Akhtar (2022)
Global environmental concerns and awareness of renewable green resources are growing demand for eco-friendly, sustainable, biodegradable natural fiber reinforced composites. Natural fibers have essential physicochemical and mechanical qualities in the composite sector. Recent interest in bamboo fiber focuses on replacing or reducing nonrenewable glass fiber as bamboo bio-composites are eco-friendly. Different processing parameters such as fiber extraction and surface modification of the composites affect the characteristics of composites. To solve the issues relating to reinforcing fibers, polymer matrix materials, and composite manufacturing procedures, various investigations on bamboo fiber bio-composites have been done in recent decades. Bamboo fiber has poor interfacial adhesion with polymer matrix and low mechanical qualities due to its hydrophilic nature. The purpose of this article is to summarize the research done on bamboo fiber bio-composites during the previous few decades. As a result, this article provides a critical review of the developments in bamboo fiber bio-composites and key results presented in the literature, with a focus on the processing procedure and ultimate properties of bamboo fibers with polymeric matrices. This research can serve as a guide for future reference on bamboo fiber reinforced composites and promote their utilization.